COMPARATIVE STUDY ON THE DEVELOPMENT OF MOTOR SKILLS -SPEED AND SKILL, IN PRIMARY CYCLE, BETWEEN RURAL AND URBAN AREA - Benedek Florian; Trofin Maria Mădălina (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In this study I have observed the development of motor skills speed and skill. I tried, taking into account the Education Law and the school curriculum, to monitor these two motor skills by applying specific means. The study was made in two classes from primary cycle, namely the 4th grade from Lower Secondary School "Irimia Irimescu", BrusturiNeamt, from rural area and the 4th grade from Lower Secondary School no.2, "Grigore Ghica-Vodă", Târgu Neamt, from urban area. Lower Secondary School "Irimia Irimescu" was the experimental group, and Lower Secondary School no.2, "Grigore Ghica-Vodă" was the witness group. As a result of evaluation samples: speed running on 25 meters, commutation 5x5 meters, long jump from the place and an application path, it was made a comparison between the evolution of the two groups.